The Role and Impact of Public-Private Partnerships in Education - Patrinos, Harry Anthony; Barrera-Osorio, Felipe; Guaqueta, Juliana (World Bank, 2012)
The book examines five ways through which public-private contracts can help countries meet education goals. First, public-private partnerships can increase access to good quality education for all, especially for poor children who live in remote, underserved communities and for children in minority populations. Second, lessons for innovative means of financing education can be particularly helpful in post-conflict countries undergoing reconstruction. Third, lessons about what works in terms of public-private partnerships contribute to the development of a more differentiated business model especially for middle-income countries. Fourth, the challenge of meeting the education Millennium Development Goals in less than a decade is a daunting one in the poorest countries. Understanding new partnership arrangements within a broad international aid architecture in education can help bring us closer to those goals. Fifth, some very innovative public-private partnership arrangements are happening in Arab countries, and lessons can be drawn from their experience.